The Saving Lie : Harold Bloom and Deconstruction - Bielik-Robson, Agata (Book collections on Project MUSE., 2011)
In this unprecedented full-length study on Harold Bloom, Agata Bielik-Robson explores the many facets of Bloom's critical writings and career. In his work, she argues, Bloom draws on a variety of disparate traditions-Judaism, Gnosis, romanticism, American pragmatism, and Freudianism, but also, especially recently, Victorian Aestheticism-that constitute a dialectical, difficult whole in constant quarrel with itself. The Saving Lie brings all these aspects of Bloom's thought together, revealing the organizing thread of "antithetical vitalism" that animates his work. Tracing the development of Bloom's vision of "life-in-antithesis" through a series of highly original and compelling readings, Bielik-Robson offers a much-needed reevaluation of a deeply complex and controversial figure. This pioneering study of Bloom and his contributions will not soon be surpassed. --Book Jacket.